Decreased sucrose content triggers starch breakdown and respiration in stored potato tubers (Solanum tuberosum) - Sonnewald, Uwe; et al. (OXFORD UNIV PRESS, 2003)
To change the hexose-to-sucrose ratio within phloem cells, yeast-derived cytosolic invertase was expressed in transgenic potato (Solanum tuberosum cv. Desiree) plants under control of the rolC promoter. Vascular tissue specific expression of the transgene was verified by histochemical detection of invertase activity in tuber cross-sections. Vegetative growth and tuber yield of transgenic plants was unaltered as compared to wild-type plants. However, the sprout growth of stored tubers was much delayed, indicating impaired phloem-transport of sucrose towards the developing bud. Biochemical analysis of growing tubers revealed that, in contrast to sucrose levels, which rapidly declined in growing invertase-expressing tubers, hexose and starch levels remained unchanged as compared to wild-type controls. During storage, sucrose and starch content declined in wild-type tubers, whereas glucose and fructose levels remained unchanged. A similar response was found in transgenic tubers with the exception,that starch degradation was accelerated and fructose levels increased slightly. Furthermore, changes in carbohydrate metabolism were accompanied by an elevated level of phosphorylated intermediates, and a stimulated rate of respiration. Considering that sucrose breakdown was restricted to phloem cells it is concluded that, in response to phloem-associated sucrose depletion or hexose elevation, starch degradation and respiration is triggered in parenchyma cells. To study further whether elevated hexose and/or hexose-phosphates or decreased sucrose levels are responsible for the metabolic changes observed, sucrose content was decreased by tuber-specific expression of a bacterial sucrose isomerase. Sucrose isomerase catalyses the reversible conversion of sucrose into palatinose, which is not further metabolizable by plant cells. Tubers harvested from these plants were found to accumulate high levels of palatinose at the expense of sucrose. In addition, starch content decreased slightly, while hexose levels remained unaltered, compared with the wild-type controls. Similar to low sucrose-containing invertase tubers, respiration and starch breakdown were found to be accelerated during storage in palatinose-accumulating potato tubers. In contrast to invertase transgenics, however, no accumulation of phosphorylated intermediates was observed. Therefore, it is concluded that sucrose depletion rather than increased hexose metabolism triggers reserve mobilization and respiration in stored potato tubers.
Keywords: invertase; potato tuber; respiration; starch breakdown; sucrose isomerase; sucrose sensing